The kinetic effect on structural behavior of mixed LiMn2O4-LiNi1/3Co1/3Mn1/3O2 cathode materials studied by in situ time-resolved X-ray diffraction technique - Yoon, Won-Sub; Nam, Kyung-Wan; Jang, Donghyuk; Chung, Kyung Yoon; Cho, Yong-Hun; Choi, Seungdon; Hanson, Jonathan C.; Yang, Xiao-Qing (ELSEVIER SCIENCE INC, 2012)
How the structural changes of each active material in mixed cathode systems take place at different charge-discharge rates is quite important in the application of the system in which the mixed cathode materials with different rate capabilities are formed into one composite electrode. Here we report the results of the real time structural change studies of mixed LiMn2O4-LiNi1/3Co1/3Mn1/3O2 composite cathode in a Li-ion cell by using in situ synchrotron-based time resolved x-ray diffraction (TR-XRD) technique. The layer structured component in the mixed composite cathode system shows less utilization at fast discharge rate (high power mode) whereas the spinel structured component is fully utilized. This clearly demonstrates that the reduced capacity at fast discharge rate for this system is caused by the less utilization of the layer structured component. The real time monitoring of the structural behavior at various discharge rates is a great tool to design the best ratios of active materials with different rate capabilities in the mixed cathode systems for different applications. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: LI-ION BATTERIES; ELECTROCHEMICAL EVALUATION; THERMAL-DECOMPOSITION; PHASE-TRANSITIONS; COMPOSITE CATHODE; LINI0.8CO0.2O2; LIMN2O4; SPINEL; OXIDE; XRD